(untitled) (Iraqi Journal of Science, 2023)
The identification of a bed’s lithology is fundamental to all reservoir characterization because the physical and chemical properties of the rock that holds hydrocarbons and/or water affect the response of every tool used to measure formation properties. The main purpose of this study is to evaluate reservoir properties and lithological identification of Nahr Umr Formation in Luhais well -12 southern Iraq. The available well logs such as (sonic, density, neutron, gamma ray, SP, and resistivity logs) are digitized using the Didger software. The petrophysical parameters such as porosity, water saturation, hydrocarbon saturation, bulk water volume, etc. were computed and interpreted using Techlog software. The lithology prediction of Nahr Umr Formation was carried out by appling IPSOM technique using density, neutron, and gamma ray logs. Nahr Umr Formation in well Luhais -12 was divided into three zones based on well logs interpretation and petrophysical Analysis: Zone-A, Zone-B, and Zone-C. The formation lithology is mainly composed of sandstone interlaminated with siltstone and shale according to interpretation of density, neutron, and gamma ray logs using IPSOM technique. Interpretation of formation lithology and petrophysical parameters shows that zone-C is characterized by clean sandstone with high porosity and water saturation whereas zone –B consists mainly of alternating shale beds with siltstone and sandstone with high porosity and water saturation less than zone –C and increasing of hydrocarbon saturation but Zone –A consists mainly of siltstone and sandstone layer with some of shale beds that contains hydrocarbon.